INCREASE OF THE CORROSION-MECHANICAL WEAR RESISTANCE OF TITANIUM ALLOYS BY NITRIDATION IN THE GLOW DISCHARGE: A REVIEW OF MODERN RESEARCH - MASHOVETS, NATALIIA; KORINNIY, ANTO; BANASHKO, TARAS (Herald of Khmelnytskyi National University. Technical sciences, 2024)
In this work, a review of modern research in the field of increasing the corrosion-mechanical wear resistance of titanium alloys using glow discharge nitriding is carried out. Titanium alloys, due to their unique properties, namely high strength, lightness, exceptional corrosion resistance and excellent biocompatibility, are widely used in aviation, medicine, engineering and many other industries. However, operational conditions in some applications require even greater improvement of the wear resistance and corrosion resistance of these alloys, which makes the search for effective methods of their improvement an urgent scientific and engineering task. Among the promising technologies that can be used to improve the corrosion-mechanical properties of titanium alloys, low-temperature anhydrous nitriding in a glow discharge should be considered. The use of low-temperature anhydrous nitriding in a glow discharge eliminates the growth of the base grain and hydrogen embrittlement of the surface. Also, low-temperature nitriding in a glow discharge makes it possible to increase the wear resistance of the surface of titanium alloys, while the saturation of the surface with nitrogen is controlled, which allows predicting the results of processing, does not lead to a change in the shape of parts.The analysis of scientific research shows that increasing the corrosion-mechanical wear resistance of titanium alloys by means of nitriding in a glow discharge is a promising direction that opens up new opportunities for industry and science. Progress in this field depends on further research, innovative development and the integration of the latest technologies, which together will contribute to the creation of more durable, efficient and environmentally friendly materials for a wide range of applications.In general, increasing the corrosion-mechanical resistance of titanium alloys by the method of nitriding in a glow discharge is a promising direction of research in Ukraine, which can lead to the improvement of the properties of titanium alloys and the expansion of their use in various industries.
Keywords: nitriding in glow discharge; corrosion-mechanical wear resistance; titanium alloys